PERAN WANITA SEBAGAI IBU DALAM PENDIDIKAN ISLAM PERSPEKTIF MURTADHA MUTHAHHARI - Wira Sugiarto; Putri Sari Ayu; Siti Al Fiza (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2023)
This research explores the thoughts of Murtadha Muthahhari (1919-1979) regarding the role of women, particularly as mothers, in providing Islamic education to children. Muthahhari, a thinker from Iran, is the central focus of this study. The aim of the research is to elaborate on Muthahhari's views regarding women's rights in accordance with their nature, with a specific focus on their role in educating children. The research methodology employed is literature review or library research. The primary data for this study are derived from the translated book by Murtadha Muthahhari titled "Filsafat Perempuan Dalam Islam: Hak Perempuan dan Relevansi Etika Sosial," while secondary data are collected from various sources such as journals, books, and websites. The research findings highlight the crucial role of women, especially as mothers, in educating children. Murtadha Muthahhari asserts that women are entitled to their rights in line with their inherent nature. Therefore, in terms of education, mothers can undertake several roles, including: 1) consuming halal and wholesome food during pregnancy, regularly reading and listening to the Quran for the fetus, 2) providing breastfeeding to infants, as it enhances intelligence and reduces the risk of specific diseases in children, 3) setting a good example for children, and 4) being the primary teacher in imparting knowledge of religion and science to children.